The Role of Environmental Accounting in Encouraging Corporate Sustainability: Literature Review - Mutmainah; Suwedy (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research aims to delve into the role of environmental accounting as a driver of corporate sustainability using a qualitative approach and literature review method. Secondary data is derived from relevant studies, and data analysis employs the literature review prism with filtering based on title, feasibility, and inclusion criteria. Findings indicate that green innovation influences environmental management accounting (EMA), subsequently affecting corporate value. The study also highlights the positive impact of using green accounting in incorporating environmental costs into the financial results of company operations. Furthermore, the relationship between coercive pressure and EMA adoption varies based on firm size, and environmental information disclosure has a direct positive impact on corporate financial performance. Implications of the research encompass both practical and conceptual recommendations. Practically, companies can leverage green innovation to reinforce environmental accounting and enhance corporate value. Additionally, understanding that firm size moderates the relationship between coercive pressure and EMA adoption can assist companies in tailoring their strategies to specific contexts. Conceptually, the study contributes to environmental accounting literature by affirming that the integration of green accounting can improve corporate financial performance.